Clima Organizacional en el Hospital General Provincial Isidro Ayora de Loja en el primer semestre de 2024: Evaluación, análisis y propuesta de mejora para 2025 - Conde Castillo, Beatriz (2024)
The primary objective of this research was to conduct a comprehensive evaluation of the organizational climate at the Isidro Ayora general Hospital in Loja, analyzing its impact on staff performance and well-being during the first semester of 2024. This analysis provides a complete view of the internal and external factors that influence employee satisfaction and the quality of service provided to patients, which is essential in a healthcare institution where team efficiency and commitment directly impact patient care. By identifying critical areas, this research aims not only to understand the current working environment but also to lay the foundation for the development of improvement strategies and institutional policies to be implemented next year, thereby fostering an optimal, healthy work environment that promotes positive outcomes for both staff and the community served by the hospital. The significance of this research is evident, as the organizational climate in the healthcare sector profoundly affects service efficiency and the well-being of providers. In an institution like Isidro Ayora general Hospital, the work environment directly influences the performance of the healthcare team and, ultimately, the quality of patient care. This study underscores the importance of creating a favorable environment for employees, as a positive work climate fosters collaboration, reduces stress, and enhances motivation. This translates into greater staff willingness to meet institutional goals and provide humanized service to patients. The research adds considerable value by highlighting the relationship between a positive organizational climate and the benefits for both individuals and the organization, giving organizational management clear guidance on which areas need strengthening and how these improvements affect the overall experience of employees and users. The methodology of this study included structured surveys and semi-structured interviews, combining a mixed approach to gain a deeper, detail-rich perspective on the hospital's organizational climate. The surveys gathered quantitative and objective data regarding job satisfaction, employee perceptions of leadership, internal communication, and team cohesion. Simultaneously, the interviews provided a qualitative perspective, capturing employees' subjective experiences, motivations, and areas they consider priorities for change. This mixed approach provided not only a holistic view but also helped identify patterns and trends across different hospital departments and hierarchical levels, enabling a thorough analysis that reveals both the strengths and weaknesses of the working environment in the hospital context. The main findings yielded clear results regarding the current state of the organizational climate, indicating several areas for improvement, particularly concerning interdepartmental communication, leadership, and recognition of employee achievements. The observed correlation between work climate and employee satisfaction was significant, underscoring that a positive work environment leads to greater commitment and better performance, while a lack of cohesion and support can reduce motivation and affect service quality. This analysis showed that employees value recognition for their efforts and clarity in expectations and roles, elements currently seen as areas of weakness within the hospital. The results suggest that implementing improvement policies for the organizational climate can lead to higher levels of employee satisfaction and well-being, as well as a positive impact on perceived quality in patient care. Finally, the improvement proposal derived from this study includes a structured action plan with specific performance indicators and an implementation schedule projected for 2025. This proposal focuses on fostering the sustainability of long-term changes, allowing for continuous impact measurement and ensuring that improvements to the organizational climate are maintained and reinforced over time. The plan prioritizes key areas such as internal communication, professional development, training, and employee recognition, building an organizational culture that values employee well-being and encourages collaboration and respect at all levels. This comprehensive strategy seeks to establish a work environment where staff feel valued and motivated, contributing to the hospital’s mission of delivering quality, humanized care and positioning Isidro Ayora general Hospital as a benchmark in organizational management within the healthcare sector. Keywords: Organizational Climate, Workplace Performance, Customer Satisfaction, Internal Communication, Continuous Improvement.